Pengaruh Konflik Peran Ganda dan Stress terhadap Komitmen Organisasi - Rina Nurlinawaty (LP2M Universitas Perjuangan Tasikmalaya, 2019)
The objectives of this research are to find out the influence of dual role conflict and stress, both simultaneously and partially, to organizational commitment of female employees Echelon IV at Tasikmalaya’s government. The method used in this research was survey method. 117 respondens from 21 institutions located at Tasikmalaya were chosen. The way of data collecting used questionnaire. Data was then analyzed using Path Analysis. The results of this research showed that there was a significant influence of dual role conflict to stress. There was a significant influence of dual role conflict, partially, to female employees’s organizational commitment. Stress has a significant influence, partially, to female employees’s organizational commitment. The dual role conflict and stress, simultaneously, have significant influences to female employees’s organizational commitment.